Development of the laser shock wave adhesion test on bonded CFRP composite. Issue 4 (11th November 2014) - Ecault, R.; Boustie, M.; Berthe, L.; Touchard, F.; Chocinski-Arnault, L.; Voillaume, H.; Campagne, B.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to develop a laser shock adhesion test (LASAT) and evaluate its ability to reveal various bond qualities of stuck carbon fiber reinforced polymer (CFRP) industrial assemblies. Design/methodology/approach – Four grades of adhesion were prepared by release agent contamination of CFRP prior to assembly. Laser shots were performed at different intensities on these samples. Findings – To characterize and quantify the damage created by the propagation of shock waves in the bonded material, several diagnoses were used (confocal microscopy, ultra-sound inspection and cross-sections microscopy). These three post-mortem techniques are complementary and provide consistent results. Originality/value – The combination of these diagnoses along with the LASAT technique provides relevant information on the bond quality in agreement with GIC values measured by the University of Patras.